Implementasi Pendekatan Culturally Responsive Teaching Guna Melatih Keterampilan Berpikir Kritis Siswa Kelas IV SD 2 Sidorejo Madiun - Pujawati, Indah; Prasasti, Pinkan Amita Tri; itjaksono, Prijo Juswo W (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
An important competency that students need to have to face the challenges of the 21st century is critical thinking skills. The aim of the research is to train students' critical thinking through the implementation of the Culturally Responsive Teaching (CRT) approach. Research data was obtained from two cycles of classroom action research (PTK) in class IV of SDN 2 Sidorejo Madiun with 12 students. Data collection was obtained from LKPD guidance scores and cognitive scores in the form of pre-test and post-test for two cycles. The results of the LKPD scores were tested with Wilcoxon and the cognitive scores were tested with N gain. The LKPD scores from both cycles increased with test results of 0.02 < 0.05, which means that there is an influence of the learning approach applied on improving students' critical thinking skills. Critical thinking indicators include interpretation, analysis and inference in the high category with mean values of 78.75 and 69 respectively. The N gain test on the cognitive value of cycle 1 is in the high category and cycle 2 is in the medium category. Students' cognitive scores from cycle 1 to cycle 2 increased by 8%. This research can be concluded that the implementation of a Culturally Responsive Teaching (CRT) based learning approach in citizenship education subjects with Pancasila element material can train students' critical thinking skills. Keywords: